MXene‐Derived Metal‐Organic Framework@MXene Heterostructures toward Electrochemical NO Sensing. Issue 50 (2nd November 2022) - Tan, Yi; Yang, Li; Zhai, Dong; Sun, Lanju; Zhai, Shengliang; Zhou, Wei; Wang, Xiao; Deng, Wei‐Qiao; Wu, Hao
Abstract: The electrochemical sensing of nitric oxide (NO) molecules by metal‐organic framework (MOF) catalysts has been impeded, to a large extent, owing to their poor electrical conductivity and weak NO adsorption. In this work, incomplete in situ conversion of V2 CTx ( T = terminal atoms) MXene to MOF is adopted, forming MOF@MXene heterostructures, which outperform MXene and MOF monocomponents toward electrochemical NO sensing. Density functional theory (DFT) calculation results indicate metal‐like electronic characters for the heterostructure benefiting from the dominating contribution of the V 3 d orbitals of the metallic MXene. Moreover, plane‐averaged charge density difference shows substantial charge redistribution occurs at the heterointerfaces, producing a built‐in field, which facilitates charge transfer. Besides, molecular mechanics‐based simulated annealing calculation reveals greatly enhanced adsorption energies of NO molecules on the heterointerfaces than that on separate MOFs and MXenes. Hence, the facilitated charge transfer and preferential NO adsorption are responsible for the dramatically promoted performance toward NO sensing. The prudent design of MOF@MXene heterostructure may spur advanced electrocatalysts for electrochemical sensing. Abstract : Incomplete conversion of MXene to metal‐organic framework (MOF) leads to the formation of MOF@MXene heterostructure, which exhibits metal‐like electronic structures contributed by the metallic MXene counterparts. Their heterointerface induces preferential NO adsorption and substantial electrons transfer from MXene inner surface to MOF species, which engage for greatly promoted electrochemical performance toward NO sensing.